Extraction and characterization of essential oil from eucalyptus leaves (eucalyptus tereticornis Sm.) as an addititive to toothpaste - Jo Christine V. Cruz. 4 0 16; 5 (2002)
u
Thesis: (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2002.
Keywords: 2 -- 0; 6; 20; 20; 2